VD_FINDINFO HC / 2019 / 360 vom 2. April 2019 - VD Tribunal cantonal (2019)
OBLIGATION D'ENTRETIEN, ENFANT, CONJOINT, CONTRIBUTION DE PRISE EN CHARGE, CHARGE FISCALE, MINIMUM VITAL | 176 al. 1 ch. 1 CC, 285 al. 1 CC, 285 al. 2 CC